Eddy-Current Nondestructive Evaluation - Bowler, Nicola (Springer Series in Measurement Science and Technology,, 2019)
This book covers the topic of eddy current nondestructive evaluation, the most commonly practiced method of electromagnetic nondestructive evaluation (NDE). It emphasizes a clear presentation of the concepts, laws and relationships of electricity and magnetism upon which eddy current inspection methods are founded. The chapters include material on signals obtained using many common eddy current probe types in various testing environments. Introductory mathematical and physical concepts in electromagnetism are introduced in sufficient detail and summarized in the Appendices for easy reference. Worked examples and simple calculations that can be done by hand are distributed throughout the text. These and more complex end-of-chapter examples and assignments are designed to impart a working knowledge of the connection between electromagnetic theory and the practical measurements described. The book is intended to equipreaders with sufficient knowledge to optimize routine eddy current NDE inspections, or design new ones. It is useful for graduate engineers and scientists seeking a deeper understanding of electromagnetic methods of NDE than can be found in a guide for practitioners.